2015
DOI: 10.1002/ajpa.22898
|View full text |Cite
|
Sign up to set email alerts
|

The role of acoustic signaling for spacing and group coordination in a nocturnal, pair‐living primate, the western woolly lemur (Avahi occidentalis)

Abstract: Our study provides first empirical evidence for a nocturnal, cohesive pair-living strepsirrhine that vocal signaling represents an important mechanism for spacing, group coordination and decision making. Findings contribute to a better understanding of the evolutionary roots of primate vocal communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Although A . occidentalis have small home ranges (median range between 1.57 ha– 1.79 ha, [ 64 ]) and rely on low quality abundant leaves, suggesting that they would be able to inhabit relatively small fragments, it is possible that the number and distribution of large trees impacts Avahi occurrence [ 63 ]. Norscia [ 63 ] found that the percentage of large trees above 3.2 cm DBH was significantly positively related to Avahi density.…”
Section: Discussionmentioning
confidence: 99%
“…Although A . occidentalis have small home ranges (median range between 1.57 ha– 1.79 ha, [ 64 ]) and rely on low quality abundant leaves, suggesting that they would be able to inhabit relatively small fragments, it is possible that the number and distribution of large trees impacts Avahi occurrence [ 63 ]. Norscia [ 63 ] found that the percentage of large trees above 3.2 cm DBH was significantly positively related to Avahi density.…”
Section: Discussionmentioning
confidence: 99%
“…Species‐specific contact calls may facilitate efficient group travel or foraging, maintain group cohesion, update group members to individual statuses of constituent group members, orient the motivational status of the group as a whole (e.g., female is still hungry, so the pair should keep traveling to access a new food patch), and coordinate behaviors (Cheney & Seyfarth, 2018; Ramanankirahina, Joly, Scheumann, & Zimmermann, 2016; Teixeira da Cunha & Byrne, 2009). Many species retain close spatial proximity with pair‐mates through nearly constant contact call use, which may be particularly useful during reduced visibility (e.g., during nocturnal foraging bouts in P. pallescens ; Kappeler, 1997).…”
Section: Multimodal Signaling Within Primate Pair‐bondsmentioning
confidence: 99%
“…In many mammalian species vocal communication is essential to coordinate social interactions such as mating rituals (e.g., [ 1 , 2 ]), alarm calling (e.g., [ 3 , 4 ]), mother-infant care (e.g., [ 5 , 6 ]), group cohesion (e.g., [ 7 , 8 ]), or territorial displays (e.g., [ 9 , 10 ]). One of the first steps towards understanding the complexity of acoustic communication in a given species is to establish a vocal repertoire [ 11 ].…”
Section: Introductionmentioning
confidence: 99%